An introduction to the South Swedish Apparent Cleft (SSAC) - Rosenkvist, Henrik (Nordlyd, 2007)
In this paper, the South Swedish Apparent Cleft (SSAC) is introduced, described and briefly discussed. The SSAC was first observed in the 1940s, and it has not yet been subject to any detailed linguistic analysis. The usage of the SSAC has been examined in a corpus study and via a questionnaire, and the results indicate, but do not confirm, that it truly is a specifically south Swedish syntactic construction. It appears in two main variants (with and without an adverbial expressing speaker attitude) and it displays a number of interesting syntactic properties (the subject must be pronominal, direct objects are disallowed, etc). From a typological perspective, there seem to be equivalent constructions in at least Japanese (no da) and English (it is that).
Keywords: cleft construction; corpus study; English; Japanese; questionnaire; South Swedish Apparent Cleft; SSAC